Thermal feedback in the high-mass star- and cluster-forming region W51 - Ginsburg, Adam; Kruijssen, Diederik (The astrophysical journal, 2017)
High-mass stars have generally been assumed to accrete most of their mass while already contracted onto the main sequence, but this hypothesis has not been observationally tested. We present ALMA observations of a ##IMG## [http://ej.iop.org/images/0004-637X/842/2/92/apjaa6bfaieqn1.gif] $3× 1.5$ pc area in the W51 high-mass star-forming complex. We identify dust continuum sources and measure the gas and dust temperature through both rotational diagram modeling of ##IMG## [http://ej.iop.org/images/0004-637X/842/2/92/apjaa6bfaieqn2.gif] $\mathrmCH_3\mathrmOH$ and brightness-temperature-based limits. The observed region contains three high-mass YSOs that appear to be at the earliest stages of their formation, with no signs of ionizing radiation from their central sources. The data reveal high gas and dust temperatures ( ##IMG## [http://ej.iop.org/images/0004-637X/842/2/92/apjaa6bfaieqn3.gif] $T\gt 100$ K) extending out to about 5000 au from each of these sources. There are no clear signs of disks or rotating structures down to our 1000 au resolution. The extended warm gas provides evidence that, during the process of forming, these high-mass stars heat a large volume and correspondingly large mass of gas in their surroundings, inhibiting fragmentation and therefore keeping a large reservoir available to feed from. By contrast, the more mature massive stars that illuminate compact ##IMG## [http://ej.iop.org/images/0004-637X/842/2/92/apjaa6bfaieqn4.gif] $\rmH\,\rmII$ regions have little effect on their surrounding dense gas, suggesting that these main-sequence stars have completed most or all of their accretion. The high luminosity of the massive protostars ( ##IMG## [http://ej.iop.org/images/0004-637X/842/2/92/apjaa6bfaieqn5.gif] $L\gt 10^4$ ##IMG## [http://ej.iop.org/images/0004-637X/842/2/92/apjaa6bfaieqn6.gif] $L_ødot $ ), combined with a lack of centimeter continuum emission from these sources, implies that they are not on the main sequence while they accrete the majority of their mass; instead, they may be bloated and cool.